2022
DOI: 10.1182/blood.2022016558
|View full text |Cite
|
Sign up to set email alerts
|

How I use platelet transfusions

Abstract: Platelet transfusions are commonly administered for the prevention or treatment of bleeding in patients with acquired thrombocytopenia across a range of clinical contexts. Recent data including randomized trials have highlighted uncertainties in the risk-benefit balance of this therapy. Hemovigilance systems report that platelets are the most frequently implicated component in transfusion reactions. There is considerable variation in platelet count increment following platelet transfusion, and limited evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…[124] One prospective study found no significant improvement in TGT and ROTEM after platelet transfusions, indicating no change in the global hemostatic potential. [122] Furthermore, platelets are the blood component most commonly associated with transfusion reactions, [125] such as fever, alloimmunization, thrombosis, and acute lung injury. [126][127][128] Febrile non-hemolytic transfusion reactions and allergic reactions may occur at a reported frequency of 1 in 14 and 1 in 50 per transfusion unit, respectively.…”
Section: Interventions To Improve Platelet Count In Patients With Cir...mentioning
confidence: 99%
“…[124] One prospective study found no significant improvement in TGT and ROTEM after platelet transfusions, indicating no change in the global hemostatic potential. [122] Furthermore, platelets are the blood component most commonly associated with transfusion reactions, [125] such as fever, alloimmunization, thrombosis, and acute lung injury. [126][127][128] Febrile non-hemolytic transfusion reactions and allergic reactions may occur at a reported frequency of 1 in 14 and 1 in 50 per transfusion unit, respectively.…”
Section: Interventions To Improve Platelet Count In Patients With Cir...mentioning
confidence: 99%
“…1 ). 30 In neonates, it has been shown that liberal transfusion of PCs increases the risk of hemorrhage and mortality. 31 32 Using PCs bears an inherent risk of alloimmunization, transfusion-transmitted infections, and allergic reactions.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…Whether new technologies based on matching genotyped blood donors and recipients, rather than the traditional labour‐intensive serological approaches, have a role in addressing and minimising risks of alloimmunisation remains unknown and is the focus of ongoing research (Haem‐Match) 29 . Another concern is the challenge in providing ABO compatible platelet transfusions 30 . There are opportunities to improve patient outcomes by expanding both the diversity of the donor pool and the methods by which we match blood transfusions.…”
Section: Recent Blood Shortages Highlight the Need To Reduce Unnecess...mentioning
confidence: 99%